Molecular Characterization and Taurine Regulation of Taurine Transporter in Goldfish. (5th February 2020) - Xiong, Ding; Jiang, Guomin; He, Zhimin; Wu, Qin; Song, Peng; Luo, Wenjie; Xu, Wenqian; Cao, Shenping; Qu, Fufa; Zhou, Yonghua; Wang, Guiqin; Liu, Zhen
Abstract: Taurine transporter (TauT) is a sodium‐ and chloride‐dependent transport carrier, and it plays a key role in the transportation of taurine. At present, the many functions of TauT in fish remain obscure. In this study, a cDNA clone for encoding a taurine transporter was isolated from Goldfish Carassius auratus . The nucleotide sequence predicted 625 amino acids with significant homology to the TauT gene of Zebrafish Danio rerio . Hydropathic analysis revealed stretches of hydrophobic amino acids that were indicative of 12 transmembrane domains that were similar to those proposed for other cloned TauT genes. The results of a reverse transcription polymerase chain reaction (RT‐PCR) analysis demonstrated that TauT broadly expressed in all of the selected tissues and developmental stages in Goldfish but with prominent differential expression levels. The expression of TauT in Goldfish has diurnal changes. The highest expression was at 1200 hours, and the lowest was at 2100 hours. Moreover, taurine treatments showed similar stimulatory effects on the expression of TauT in the intestines of Goldfish both in vitro and in vivo. Overall, these results may provide new insights into the regulation of TauT expression in fish, which has potential applications for improving fish dietary formulations.